New species of Quiva (Paraquiva) Cadena-Castañeda & Gorochov, 2013 (Orthoptera: Tettigoniidae: Phaneropterinae: Dysoniini) from Brazilian Amazon Rainforest - de Mello Mendes, Diego Matheus (Zootaxa, 2022)
The genus Quiva belongs to the tribe Dysoniini (Phaneropterinae: Tettigoniidae) and is divided into two subgenera and seven species: Quiva (Quiva) with six species and Quiva (Paraquiva) with only one species, Quiva (Paraquiva) angieae which currently only is known for the type locality (Leticia-Colombia). This work describes the new species Quiva (Paraquiva) obscura sp. nov. for the Amazon and the first record of the subgenus for Brazil is made. A distribution map for the subgenus and comments on the natural history of the new species are provided.